Prescolarisation Et Developpement Des Apprentissages Fondamentaux A L’ecole Primaire Ivoirienne. Une Analyse Comparee D’enfants De Milieux Differents - Thierry, Seka Yapi Arsène (European Scientific Journal, ESJ, 2016)
Pre schooling is an institutionalized period of pre learning where child coordinates his sense, to adjust his actions to reach to read and write in teaching language; French. But although an unequal repartition of schools garden, and mostly not having attended these schools, some children reach to read and write as well as possible in French language. This research gave the occasion to compare oral and written productions of children according their status (pre scolarised and not pre scolarised). The aim is to evaluate the two children group’s performance on oral and written knowing that one group live in town so has attended garden school and the other group live in campaign where there is no garden. The hypothesis according which, there is a bound between attending garden and developing of children’s performance shows that there is a deep difference between the two groups of children. The one who attended garden school are talented in reading whereas they who are in campaigns succeed more in writing.